Biodiversity of Endophytic Bacteria from Egg Plant in Lowland - Purnawati, Arika; Nirwanto, Herry (Nusantara Science and Technology Proceedings, 2020)
Endophytic bacteria are a group of microbes that live in plant tissues without causing negative effects and don’t cause sick on plants, are found in various plants, and can be isolated from all parts of the plant: roots, stems, and seeds. Endophytic bacteria in nature, have high diversity because in a single plant can be found more than one kind of endophytic bacteria, so many plants found many kinds of endophytic bacteria. Endophytic bacteria that have been isolated and identified from eggplants. This study aimed to isolate endophytic bacteria from eggplants in lowland Kandat Kediri. Crop sampling was conducted using a systematic random method. The research stages are surveys and microbial isolation of endophytes. Isolation is done from the stems of a healthy eggplant around the sick eggplant. The crop samples were then washed with running water and cut 1-3 cm. The cutting was sterilized by ethanol 70% (30 sec), sodium hypochlorite 5% (5 min), ethanol 70% (30 sec) and rinsed with sterile water (3 minutes). The results are from the stem get 10 isolates of endophytic bacteria that have different characteristics.